Optimizing plum drying: influence of ripening stages on cell wall composition, water status, drying characteristics, and phenolic profiles - Xiaohua Li; Wenjuan Tang; Jinkui Sun; Yulan He; Guogang Chen; Chunhui Shan; Fan Lai (Food Production, Processing and Nutrition)
Abstract Plums (Prunus domestica L.) are highly valued for their nutritional benefits, antioxidant properties, and economic significance in the dried fruit industry. However, optimizing their drying process while preserving bioactive compounds remains a challenge due to the structural and biochemical changes occurring during ripening. Although extensive research has been conducted on post-harvest drying techniques of plums, the influence of ripening on fruit physicochemical properties, which in turn affects drying characteristics and final dried product quality, has not been sufficiently explored. In this study, plums were categorized into six ripening stages (S1–S6), and their physicochemical characteristics, enzymatic activities, polysaccharide composition, water mobility, drying behavior, and phenolic profiles were systematically analyzed. Results indicated that enzymatic activities of pectin methylesterase, polygalacturonase, and cellulase increased with ripening, leading to cell wall degradation and enhanced water mobility. Chlorogenic acid, quercetin, and procyanidin B1 were the dominant phenolic compounds, with the highest concentrations observed at the S4 stage. The S4 stage exhibited the shortest drying time (12.9 h) and lowest specific energy consumption (7.65 kW·h/kg), while retaining the highest total phenolics (40.19 mg/g DW), ascorbic acid (40.27% retention), and antioxidant activity. Overripe plums (S5–S6) suffered from structural collapse, prolonged drying, and significant phenolic degradation. This study highlights the critical role of ripening in optimizing drying efficiency and bioactive compound retention, providing a novel approach to improving dried plum quality. Graphical Abstract